Participatory systems science for enhancing health and wellbeing in the Indian Ocean territories - Allender, Steven; Munira, Syarifah Liza; Bourke, Siobhan; Lancsar, Emily (Frontiers in Public Health, 2023)
Objectives Co-creation of diabetes and obesity prevention with remote communities allows local contextual factors to be included in the design, delivery, and evaluation of disease prevention efforts. The Indian Ocean Territories (IOT) comprise the Christmas (CI) and Cocos Keeling Islands (CKI) and are remote Australian external territories located northwest of the mainland. We present results of a co-design process conducted with residents of IOT using realist inquiry and system mapping. Methods Interviews with 33 community members (17 CI, 14 CKI, 2 off Islands) on causes and outcomes of diabetes (2020/21) comprising community representatives, health services staff, dietitians, school principals and government administrators. Interviews were used to create causal loop diagrams representing the causes of diabetes in the IOT. These diagrams were used in a participatory process to identify existing actions to address diabetes, identify areas where more effort would be valuable in preventing diabetes, and to described and prioritize actions based on feasibility and likely impact. Findings Interviews identified 31 separate variables categorized into four themes (structural, food, knowledge, physical activity). Using causa loop diagrams, community members developed 32 intervention ideas that included strengthening healthy behaviors like physical activity, improving access to healthy and culturally appropriate foods, and overcoming the significant cost and availability limitations imposed by remoteness and freight costs. Interventions included relatively unique Island issues (e.g., freight costs, limited delivery timing), barriers to healthy food (e.g., limited fresh food availability), physical activity (e.g., transient workforce) and knowledge (e.g., multiple cultural backgrounds and language barriers, intergenerational knowledge).